Stylistic Manifestations in Sayyid Qutb’s Interpretation of the Shadows: Voice Variations as a Model - Mohsin Sulaiman Saeed Aziz; Salih Mala Aziz (Zanco Journal of Human Sciences, 2026)
This study presents a stylistic reading of the phenomenon of phonetic variations in Sayyid Qutb's In the Shade of the Qur'an (In the Shade of the Qur'an), describing them as rhythmic mechanisms that operate semantically and are not understood as verbal ornamentation. The study reorganizes Qutb's references into a procedural classification of rhythmic patterns (general rhythm, interval rhythm, rhythmic coherence, successive waves, etc.) and links them to observable indicators such as interval length, rhyme closure, degrees of parallelism and repetition, and letter characteristics. Textual comparisons demonstrate that the shift in subject and scene within the surah is accompanied by a calculated change in rhythmic meter and interval formulation, deepening the surah's artistic unity and controlling its emotional impact. The results contribute to transforming scattered observations into an applicable and comparable model, and paving the way for integration with performance studies and computational analysis of rhythm.